Making Adaptation Measurable: CGIAR, the Global Goal on Adaptation, and the COP30 Outcome - Miranda, Daniela; Salfi, Laura (2026)
This blog details how CGIAR played a direct role in shaping the Global Goal on Adaptation (GGA) outcome at COP30, contributing scientific expertise to the development of the Belém Adaptation Indicators under the United Arab Emirates–Belém work programme.